Omega-3 (n-3) fatty acids, cardiovascular disease and stability of atherosclerotic plaques - Calder, P. C.; Yaqoob, P. (Cellular and Molecular Biology, 2010)
Long-chain n-3 polyunsaturated fatty acids are found in oily fish and in fish oils and similar preparations. Substantial evidence from epidemiological and case-control studies indicates that consumption of fish, oily fish and long-chain n-3 fatty acids reduces risk of cardiovascular mortality. Secondary prevention studies using long-chain n-3 fatty acids in patients post-myocardial infarction have shown a reduction in total and cardiovascular mortality with an especially potent effect on sudden death. Long-chain n-3 fatty acids have been shown to beneficially modify a range of cardiovascular risk factors, which may result in primary cardiovascular prevention. However, reduced non-fatal and fatal events and a reduction in sudden death probably involve other mechanisms. Reduced thrombosis following long-chain n-3 fatty acids may play a role. A decrease in arrhythmias is a favoured mechanism of action of long-chain n-3 fatty acids and is supported by cell culture and animal studies. However human trials using implantable cardiac defibrillators have produced inconsistent findings and a recent meta-analysis does not support this mechanism of action. An alternative mechanism of action may be stabilisation of atherosclerotic plaques by long-chain n-3 fatty acids. This is suggested by one published human study which showed that incorporation of long-chain n-3 fatty acids into plaques collected at carotid endarterectomy resulted in fewer macrophages in the plaque and a morphology indicative of increased stability. These findings are supported from observations in an animal model and suggest that the primary effect of long-chain n-3 fatty acids might be on macrophages within the plaque.